The degree to which mathematics teachers in Al-Madinah Al-Munawwara practice constructivist theory at the elementary level - Alrehaili, Hamza Faisal (Journal of Curriculum and Teaching Methodology, 2025)
This study aimed to identify the extent to which mathematics teachers in Madinah practice constructivist theory at the elementary level and examine the significance of differences in the average degree of their practice based on the variables of experience and the teacher’s score on the General Educational Test for the Professional License for Teaching Positions. The study adopted a descriptive survey methodology and used a questionnaire as the primary tool. The study yielded several findings, including that there are no statistically significant differences at the level (α ≥ 0.05) in the average degree of mathematics teachers’ practice of constructivist theory in Madinah attributed to the gender variable. However, there are statistically significant differences at the level (α ≥ 0.05) in the average degree of their practice attributed to the variable of years of service. Additionally, there are no statistically significant differences at the level (α ≥ 0.05) in the average degree of their practice attributed to the variable of the teacher’s score on the General Educational Test for the Professional License for Teaching Positions. The study provided several recommendations, the most important of which are the need to enhance training on constructivist learning strategies by offering training courses for teachers to improve their skills in applying constructivist teaching methods, especially for less experienced teachers. It also emphasized the importance of encouraging the application of authentic assessment, as it is crucial to motivate teachers to regularly use authentic assessment, as it supports the application of acquired knowledge in real-life situations.
Keywords: Teaching Practices; Constructivist Theory; Mathematics Teachers